2020
DOI: 10.3748/wjg.v26.i23.3170
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the ellagic acid-derived gut microbiota metabolite – Urolithin A in gastrointestinal protection

Abstract: Urolithin A (UA) is a metabolic compound generated during the biotransformation of ellagitannins by the intestinal bacteria. The physiologically relevant micromolar concentrations of UA, achieved in the plasma and gastrointestinal tract (GI) after consumption of its dietary precursors, have been revealed to offer GI protection. The health benefit has been demonstrated to be principally related to anticancer and anti-inflammatory effects. UA has been shown to possess the capability to regulate multiple tumor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 57 publications
(86 reference statements)
1
32
0
Order By: Relevance
“…Furthermore, reduced numbers of apoptotic cells within the colon of verum versus placebo treated mice point towards cell-protective effects of urolithin-A in the intestinal tract during C. jejuni infection. In support, both urolithins and the ellagitannins were shown to suppress apoptosis in inflammation [ 31 , 42 , 43 ]. Anti-apoptotic effects of urolithin-A are also in agreement with the finding that urolithin-A improved chemically induced colitis by activation of nuclear factor erythroid 2–related factor 2 (Nrf 2) dependent intestinal epithelial barrier functions and aryl-hydrocarbon receptor induced anti-inflammatory and anti-oxidative cellular pathways [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reduced numbers of apoptotic cells within the colon of verum versus placebo treated mice point towards cell-protective effects of urolithin-A in the intestinal tract during C. jejuni infection. In support, both urolithins and the ellagitannins were shown to suppress apoptosis in inflammation [ 31 , 42 , 43 ]. Anti-apoptotic effects of urolithin-A are also in agreement with the finding that urolithin-A improved chemically induced colitis by activation of nuclear factor erythroid 2–related factor 2 (Nrf 2) dependent intestinal epithelial barrier functions and aryl-hydrocarbon receptor induced anti-inflammatory and anti-oxidative cellular pathways [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of the here-obtained preclinical results to defined treatment measures of human campylobacteriosis are supported by the fact that anti-inflammatory and gut epithelial barrier strengthening functions of urolithins and ellagitannin precursors have been confirmed in humans recently [ 42 ]. Furthermore, urolithin-A has been shown to exert potent gut protective functions [ 43 ], and safety evaluation in humans and rats revealed the complete absence of unwanted side effects [ 53 ]. Hence, patients suffering from campylobacteriosis may benefit from the ingestion of urolithin precursors in walnuts and pomegranate juice, which are cheap and easily accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the therapeutic potential of available delivery systems to enhance EA bioavailability, innovative and novel formulations that can eliminate the hepatic first-pass pharmacokinetic effect and uphold optimal effective concentrations of EA in the systemic circulation is desirable (Espín, Larrosa, García-Conesa, & Tomás-Barberán, 2013). Current research is also shifting the paradigm to understanding EA's bioavailability and its derivatives (UTs or UGs) in the prevention and treatment of chronic liver diseases (Kujawska & Jodynis-Liebert, 2020;Evtyugin et al, 2020;Kang, Buckner, et al, 2016;Kang, Espín, et al, 2016). Furthermore, understanding the systemic diversity, biotransformation (UTs or UGs), and bioactivity of EA in humans will favour quickening the focus on their additive, synergistic, or antagonistic effect with other phytochemicals for clinical development.…”
Section: Bioavailability Of Eamentioning
confidence: 99%
“…It is these findings that have paved the way for their use in clinical trials in multiple types of cancer (Peiffer, 2018). More recent work has demonstrated that BRB and their components also modulate the host microbiome in a positive manner (Chen et al., 2018; Giménez‐Bastida et al., 2020; Gu et al., 2019; Kujawska & Jodynis‐Liebert, 2020; Pan et al., 2018; Pan et al., 2017; Wang et al., 2009). On the other hand, others have reported that traditional chemotherapies including platinum based therapeutics and taxanes, negatively affect the host gut flora, leading to dysbiosis and increased morbidity and mortality during cancer therapy (Alexander et al., 2017; Hong et al., 2019; Kim et al., 2018; Molinero et al., 2019; Sartor & Wu, 2017; Yadav et al., 2018).…”
Section: Dicussion/conclusionmentioning
confidence: 99%
“…A new emerging pathway in which BRB and their components may positively affect cancer outcomes is through modulation of the host microbiome (Chen et al., 2018; Gu et al., 2019; Pan et al., 2018). These include the polyphenolic anthocyanins (AC, 23, 24) and their active metabolite protocatechuic acid (Gu et al., 2019; Peiffer et al., 2014), as well as the active metabolites of ellagic acid, the urolithins (Giménez‐Bastida, Ávila‐Gálvez, Espín, & González‐Sarrías, 2020; Gu et al., 2019; Kujawska & Jodynis‐Liebert, 2020). In parallel with these findings, other groups have demonstrated that ones microbiome may affect their response to chemotherapy including colonic, breast, and pancreatic cancers (Khodavirdipour, Jamshidi, Nejad, Zandi, & Zarean, 2020; Shvets, Lukianova, & Chekhun, 2020; Zhang, Gao, Li, Wang, & Liu, 2020).…”
Section: Introductionmentioning
confidence: 99%